1982
DOI: 10.1177/000992288202100805
|View full text |Cite
|
Sign up to set email alerts
|

How do Hyperactive Children Feel About Taking Stimulants and Will They Tell the Doctor?

Abstract: There are no systematic data on the attitudes of hyperactive children toward treatment with stimulant medication. Such knowledge would be of aid to the physician in understanding the child, structuring therapy, and improving compliance; therefore we interviewed 52 hyperactive children who had been so treated. The outstanding findings were that a large fraction of the children disliked the medication and often tried to avoid taking it. The physician interview provides valuable information with some children, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 5 publications
0
36
0
1
Order By: Relevance
“…Given data that show the unique perspectives of children and adolescents regarding ADHD treatment, research is needed to understand the impact of their preferences and goals on treatment initiation and outcomes. [35][36][37][38][39][40] Although the instrument used in this study was validated as a measure of goals, we did not simultaneously administer a validated measure of goal attainment. Additional work is needed to confirm that a decrease in goal scores on the ADHD PGI definitively represents goal attainment.…”
Section: Discussionmentioning
confidence: 99%
“…Given data that show the unique perspectives of children and adolescents regarding ADHD treatment, research is needed to understand the impact of their preferences and goals on treatment initiation and outcomes. [35][36][37][38][39][40] Although the instrument used in this study was validated as a measure of goals, we did not simultaneously administer a validated measure of goal attainment. Additional work is needed to confirm that a decrease in goal scores on the ADHD PGI definitively represents goal attainment.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of adherence among ADHD children and adolescents are reportedly very poor, ranging from 35 to 81 %, depending on the methodology applied and the follow-up length [4,8,14,24,34,47,52]. The MTA study showed adherence rates of 63 % at 14 months, though the percentage dropped to less than one-third after 8 years of follow-up [38,41].…”
Section: Introductionmentioning
confidence: 99%
“…Un estudio muestra que, aunque rara vez se quejaban a sus médicos, el rechazo era generalizado a la toma del estimulante, y describían su experiencia con expresiones como "me hace triste", "se apodera de mí", "nada me hace reír", "no me deja sentirme como soy", etc. (Sleator, Ullmann y von Neumann, 1982). No parece gustarles el fármaco, expresan sentirse infelices y desean estar como antes de tomarlo (Eichlseder, 1985).…”
Section: De La Experiencia Subjetiva Del Paciente Tda/h En Tratamientunclassified